Effect of saturation alteration on wellbore stability during WAG Injection - Bataee, M. (Society of Petroleum Engineers, 2017)
Nowadays, enhanced oil recovery (EOR) injection methods are very popular due to its simplicity and effectiveness in increasing the recovery. The water alternating gas (WAG) injection method shows higher sweep efficiency and recovery than the one-phase fluid injection. However, extremely high injection pressure will fracture the wellbore. Moreover, the saturation alteration changes the rock mechanical properties and stress values around the wellbore. The purpose of this study is to study the effects of saturation alteration on wellbore stability. This study has implemented with modelling procedure regarding the obtained experimental results from modified triaxial testing device. The core holder for this device is exclusively designed to prepare the favourable data of rock mechanical properties for different saturation schemes. The parameters of pressures, saturations, and stresses were obtained for the WAG flow using numerical modelling. For the pressures and saturation values, finite difference method (FDM) was used and to solve the rock stress values, finite volume method (FVM) was applied. According to experimental results, the recorded maximum axial stress was higher than the water and oil saturated cases (48.19 respected to 42.33 and 41.28). It indicates that the formation was more resistive to failuire for gas injection. However, after modelling, it was concludedthat the formation was more unstable in the gas injection case because of higher pressure transient. Therefore, the possibility of wellbore failure was higher during gas injection rather than water injection. Copyright 2017, Society of Petroleum Engineers.